Self-care or assisted PD: development of a new approach to evaluate manual peritoneal dialysis practice ability. Issue 1 (31st December 2022) - Huang, Jiaying; Gu, Aiping; Li, Na; He, Yanna; Xie, Weizhen; Fang, Wei; Yuan, Jiangzi; Jiang, Na
Abstract: Background: Peritoneal dialysis (PD) is a home-based therapy which requires the patients or their caregivers to perform the practice. We aimed to develop a practical approach to evaluate PD practice ability of the patients and to identify berries to self-care PD. Methods: A structural form was designed comprising measures of physical, cognitive, and operational abilities which were required to perform manual PD independently. The evaluation was jointly conducted by a PD nurse, a nephrologist and a close family member of the patient. Patients who met all the requirements were deemed as capable of performing PD independently (self-care PD) and others were deemed as needing an assistant (assisted PD). Results: The evaluation form was applied in 280 prevalent PD patients and 33.9% of them were assessed as needing assisted PD, mainly due to physical (62.1%) or operational (66.3%) disabilities. The evaluation result was consistent with current dialysis status in 79.3% patients and it matched better in patients who performed PD with the help of an assistant (93.0 vs. 76.8%, p = 0.014). Patients who were evaluated as having barriers to self-care PD but still performed PD without an assistant were older and demonstrated higher prevalence of diabetic nephropathy and PD-related infection, lower education level, and lower serum albumin ( p < 0.05). Conclusions: The PD practice ability assessment form is useful to identify patients with barriers to self-care PD. It provides objective information to the patients and their family to choose feasible PD practice modality, self-care, or assisted PD.